Spiritual bankruptcy a prophetic call to action - Cobb, John B. (Nashville, Tenn. : Abingdon Press, 2010)
In these times many people feel that their cherished religious values are held hostage by the forces of secularization and that, as a consequence, society is morally bankrupt. While acknowledging this problem, John Cobb overturns the prevailing expectations by drawing a distinction between secularization and secularism. Secularization, as Cobb uses the term, has a prophetic function. It is a process by which religion is cleansed and refocused on mission and ministry rather than on other-worldly myths and concerns. The uncritical understanding of religion that focuses on religion for its own sake is what Cobb calls secularism. In Cobb's view, secularization has led to secularism or a culture of consumerism that threatens those very religious convictions many hold dear. After teasing the concepts of secularization and secularism apart, Cobb proposes an alternate path for secularization that will help us reevaluate our relation to our world and each other.
Preface -- In confronting catastrophe, who can help? -- Our heritage from Greece and Israel -- Religiousness and secularizing in the church -- The rise of secularism -- The secularist intention of modern philosophy -- Secularist education -- The discipline of economics and the triumph of economism -- Reactions to secularism -- A new beginning in philosophy -- Secularizing Christianity in the United States.
Includes bibliographical references.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Christianity and culture; Secularism; Secularization (Theology); Christianity and culture; Secularism; Secularization (Theology); RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books